Aqueous SDS micelle-promoted acid-catalyzed domino ABB’ imino Diels-Alder reaction: a mild and efficient synthesis of privileged 2-methyltetrahydroquinoline (2013)
New green protocol for the efficient synthesis of pharmacologically relevant 4-amidyl-2-methyl-1,2,3,4-tetrahydroquinolines (THQs) through the domino type ABB’ imino Diels–Alder reaction in acidified water in the presence of sodium dodecyl sulphate (SDS) surfactant was developed for the first time. The influence of the SDS micelles and their different concentrations (5.0, 8.2 and 12.0 mM) on reactivity of the imino Diels–Alder reaction was studied. It was found that the best THQ yields (70–99%) are achieved above the critical micellar concentration (12 mM) using pH 1.0–2.5. This procedure resulted in a general and clean environmentally benign protocol to obtain the privileged diastereospecific cis 2,4-disubstituted THQ molecules of highest biological interest.